Causes and importance of new particle formation in the present‐day and preindustrial atmospheres. Issue 16 (24th August 2017) - Gordon, Hamish; Kirkby, Jasper; Baltensperger, Urs; Bianchi, Federico; Breitenlechner, Martin; Curtius, Joachim; Dias, Antonio; Dommen, Josef; Donahue, Neil M.; Dunne, Eimear M.; Duplissy, Jonathan; Ehrhart, Sebastian; et al.
Abstract: New particle formation has been estimated to produce around half of cloud‐forming particles in the present‐day atmosphere, via gas‐to‐particle conversion. Here we assess the importance of new particle formation (NPF) for both the present‐day and the preindustrial atmospheres. We use a global aerosol model with parametrizations of NPF from previously published CLOUD chamber experiments involving sulfuric acid, ammonia, organic molecules, and ions. We find that NPF produces around 67% of cloud condensation nuclei at 0.2% supersaturation (CCN0.2%) at the level of low clouds in the preindustrial atmosphere (estimated uncertainty range 45–84%) and 54% in the present day (estimated uncertainty range 38–66%). Concerning causes, we find that the importance of biogenic volatile organic compounds (BVOCs) in NPF and CCN formation is greater than previously thought. Removing BVOCs and hence all secondary organic aerosol from our model reduces low‐cloud‐level CCN concentrations at 0.2% supersaturation by 26% in the present‐day atmosphere and 41% in the preindustrial. Around three quarters of this reduction is due to the tiny fraction of the oxidation products of BVOCs that have sufficiently low volatility to be involved in NPF and early growth. Furthermore, we estimate that 40% of preindustrial CCN0.2% are formed via ion‐induced NPF, compared with 27% in the present day, although we caution that the ion‐induced fraction of NPF involving BVOCs is poorly measured at present. Our model suggests that the effect of changes in cosmic ray intensity on CCN is small and unlikely to be comparable to the effect of large variations in natural primary aerosol emissions. Plain Language Summary: New particle formation in the atmosphere is the process by which gas molecules collide and stick together to form atmospheric aerosol particles. Aerosols act as seeds for cloud droplets, so the concentration of aerosols in the atmosphere affects the properties of clouds. It is important to understand how aerosols affect clouds because they reflect a lot of incoming solar radiation away from Earth's surface, so changes in cloud properties can affect the climate. Before the Industrial Revolution, aerosol concentrations were significantly lower than they are today. In this article, we show using global model simulations that new particle formation was a more important mechanism for aerosol production than it is now. We also study the importance of gases emitted by vegetation, and of atmospheric ions made by radon gas or cosmic rays, in preindustrial aerosol formation. We find that the contribution of ions and vegetation to new particle formation was also greater in the preindustrial period than it is today. However, the effect on particle formation of variations in ion concentration due to changes in the intensity of cosmic rays reaching Earth was small. Key Points: New particle formation produces over half of CCN in the present‐day and preindustrial atmospheres BVOCs are more important to CCN formation than previously thought Our current ion‐induced nucleation rates imply only small changes of CCN over the solar cycle